Application experience of the concept of membranous nature in the microsurgery of vestibular schwannoma - GAO Peng; ZHOU Lü; WANG Bin; LI Zhi⁃fan; XIAO Jin; CHENG Hong⁃wei (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To explore the application of membranous concept in vestibular schwannoma surgery. Methods A total of 39 patients with vestibular schwannoma who received membranous surgical treatment in The First Affiliated Hospital of Anhui Medical University from May 2020 to June 2021 were enrolled. Through the retrosigmoid approach, the intraoperative electrophysiological monitoring was performed, and the membranous concept was used to separate the brain stem of the tumor and the interface between the tumor and the facial nerve and the cochlear nerve. Facial nerve function was evaluated by the House⁃Brackmann (H⁃B) grade and hearing was evaluated by the American Academy of Otolaryngology⁃Head and Neck Surgery（AAO⁃HNS）scale at one day, one week and one year after surgery. Results Total resection was performed in 31 cases (79.49%) and nearly total resection in 8 cases (20.51%). Facial nerve anatomical preservation was achieved in all patients, and facial nerve function returned to normal or nearly normal (H⁃B grade Ⅰ-Ⅱ) 84.62% (33/39), moderate facial paralysis (H⁃B grade Ⅲ) 10.27% (4/39), moderate and severe facial paralysis (H⁃B grade Ⅳ) 5.13% (2/39) on the first day after surgery. One week after surgery, 71.79% (28/39) of patients with normal or nearly normal facial nerve function, 15.38% (6/39) of moderate facial paralysis, 10.27% (4/39) of moderate and severe facial paralysis, and 2.56% (1/39) of severe facial paralysis (H⁃B grade Ⅴ). One year after surgery, 92.31% (36/39) of patients with facial nerve function returned to normal or nearly normal, 5.13% (2/39) of patients with moderate facial paralysis, and 2.56% (1/39) of patients with moderate and severe facial paralysis. Among the 10 patients (25.64%) who retained effective hearing before surgery (AAO⁃HNS grade≥C), there were 4, 3 and 6 cases at one day, one week and one year after surgery, respectively. Those who did not retain effective hearing before surgery did not recover effective hearing after surgery. According to the comparison of tumor volume and nature, the proportion of patients with normal facial nerve function (H⁃B grade Ⅰ) in the tumor volume≤3 cm group was higher than that in＞3 cm group [12/18 vs. 19.05% (4/21); Fisher's exact probability: P=0.006], the proportion of patients with normal facial nerve function in the solid tumor group was higher than that in cystic group [71.43% (15/21) vs. 1/10; Fisher's exact probability: P=0.010] at one year after surgery. Conclusions The membranous concept in vestibular schwannoma surgery can protect facial nerve function well, and has a positive effect on the protection of cochlear nerve and brain stem.